The Impact of Intraoperative Vasopressor Use and Fluid Status on Flap Survival in Traumatic Lower Extremity Reconstruction - Roohani, Idean; Moshal, Tayla; Boudiab, Elizabeth M.; Stanton, Eloise W.; Zachary, Paige; Lo, Jessica; Carey, Joseph N.; Daar, David A. (Journal of Reconstructive Microsurgery, 2024)
Background Historically, the use of intraoperative vasopressors during free flap lower extremity (LE) reconstruction has been proposed to adversely affect flap survival due to concerns about compromising flap perfusion. This study aims to analyze the impact of intraoperative vasopressor use and fluid administration on postoperative outcomes in patients undergoing traumatic LE reconstruction.Methods Patients who underwent LE free flap reconstruction between 2015 and 2023 at a Level I Trauma Center were retrospectively reviewed. Statistical analysis was conducted to evaluate the association between vasopressor use and intraoperative fluids with partial/complete flap necrosis, as well as the differential effect of vasopressor use on flap outcomes based on varying fluid levels.Results A total of 105 LE flaps were performed over 8 years. Vasopressors were administered intraoperatively to 19 (18.0%) cases. Overall flap survival and limb salvage rates were 97.1 and 93.3%, respectively. Intraoperative vasopressor use decreased the overall risk of postoperative flap necrosis (OR 0.00005, 95% CI [9.11 × 10−9–0.285], p = 0.025), while a lower net fluid balance increased the risk of this outcome (OR 0.9985, 95% CI [0.9975–0.9996], p = 0.007). Further interaction analysis revealed that vasopressor use increased the risk of flap necrosis in settings with a higher net fluid balance (OR 1.0032, 95% CI [1.0008–1.0056], p-interaction =0.010).Conclusion This study demonstrated that intraoperative vasopressor use and adequate fluid status may be beneficial in improving flap outcomes in LE reconstruction. Vasopressor use with adequate fluid management can optimize hemodynamic stability when necessary during traumatic LE microvascular reconstruction without concern for increased risk of flap ischemia.
Keywords: lower extremity; free flap; vasopressor; intraoperative fluids